Perilaku Pencegahan COVID-19 Pada Tenaga Kesehatan Puskesmas Dalam Masa Pandemi di Indonesia Tahun 2020 - Meiliyana, Lia; Damayanti, Rita (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2021)
Background. COVID-19 is a new contagious disease emerging in December 2019 and turned into a pandemic in 2020. Health workers are on the front line against COVID-19. The death rate for health workers in Indonesia is the third-highest globally (as of 27 January 2021); therefore, it is necessary to analyze the factors from a behavioral aspect. Objective. to analyze the prevention behavior of COVID-19 among health workers at health centers (puskesmas) during the pandemic in Indonesia in 2020 using the Health Belief Model. Method. used a cross-sectional approach on secondary data of collaboration PPPKMI PPKFKM UI in the June 2020 survey. Selected variables consist of modification factors, perceived threats, perceived barriers, and cues to action. Results. The proportion of respondents that always wear a mask when leaving the house was 93,7%, at work 96.2%, always wash hands 90%, and always keep a distance 86.7%. The average of practicing preventive behavior was 97,75 points (scale 100). Independent variables that have a significant relationship with COVID-19 prevention behavior are gender (p-value=0,003;OR.2,056), knowledge (p-value=0,032;OR.0,603) and perceived barriers (p-value=0,0001 OR.2,080). Conclusion. This study found that perceived barriers were the most influencing factor on COVID-19 prevention behavior among health workers at Puskesmas.